-7(s+10)+11=-5s-6

Simple and best practice solution for -7(s+10)+11=-5s-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(s+10)+11=-5s-6 equation:


Simplifying
-7(s + 10) + 11 = -5s + -6

Reorder the terms:
-7(10 + s) + 11 = -5s + -6
(10 * -7 + s * -7) + 11 = -5s + -6
(-70 + -7s) + 11 = -5s + -6

Reorder the terms:
-70 + 11 + -7s = -5s + -6

Combine like terms: -70 + 11 = -59
-59 + -7s = -5s + -6

Reorder the terms:
-59 + -7s = -6 + -5s

Solving
-59 + -7s = -6 + -5s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '5s' to each side of the equation.
-59 + -7s + 5s = -6 + -5s + 5s

Combine like terms: -7s + 5s = -2s
-59 + -2s = -6 + -5s + 5s

Combine like terms: -5s + 5s = 0
-59 + -2s = -6 + 0
-59 + -2s = -6

Add '59' to each side of the equation.
-59 + 59 + -2s = -6 + 59

Combine like terms: -59 + 59 = 0
0 + -2s = -6 + 59
-2s = -6 + 59

Combine like terms: -6 + 59 = 53
-2s = 53

Divide each side by '-2'.
s = -26.5

Simplifying
s = -26.5

See similar equations:

| 6y+10=4+6y+6 | | .55x=2 | | 24-8x=1-11x | | 4-2(3x-5)+x=7(1-3x) | | 1/3h+4=8 | | y=(x-4)/5 | | 3-2(x-1)+4x=5-(2-x) | | -2/3(6x-12y) | | 9(t-9)-11=-6t+10 | | 5w+2=-1+3(w-10) | | X/3-21=14 | | 4-2(3x-5)+x=7-(1-3x) | | X/6-17=14 | | 3x-2(x+4)=2x-3 | | 5x+-5=20 | | 8W+2W-7=23 | | 7+4x-4t=-11 | | 19x-13=25 | | 8x-2+3x=5x+10 | | (2+(2-(2+(2-(2+r)))))=1 | | -7y-2=-6y-6 | | 3(2+5x)+3=2(1-3x) | | 2x+3(1x-10)=45 | | (x^2+1)= | | 2x+3(x-10)=-45 | | y=-0.2*x+520.4 | | 1x-5(x+2)=26 | | 6*6+7= | | 2sen^2x-senx-1=0 | | 5/678 | | 5/6.35 | | 5/6•35 |

Equations solver categories